Child Neuropsychology - Semrud-Clikeman, Margaret; Ellison, Phyllis Anne Teeter (Springer, 2007)
The human brain represents the product of an ongoing, six-billion-year construction project. In its physical form and function, the human brain represents millions upon millions of trial-and-error adaptive adjustments. Comprised of an estimated 100 billion neurons and many more glial cells it is organized into thousands of regions. The human brain, in a seamlessly integrated manner, governs body functions and movement but more importantly, regulates cognition. Not surprisingly, although the brains of different animals may not look exactly alike, they all work according to the same principles and mechanisms. These neurons and glial cells communicate using a nearly infinite number of synaptic connections, yet the entire organ in humans weighs only about three pounds. As authors Sandra Aamodt and Sam Wang eloquently describe in their book, Welcome to your brain (2007), billions of years of evolution have resulted in a very complex human brain, yet one that is a jumbled, far from efficient, crowded organ. They describe the neuronal pathways of the human brain as the equivalent of the New York City subway system or the streets of London with layers upon layers of routes each constructed at a different time in a different way. Yet this stunning system, for the most part, develops and works fine for most children.
Assessment and Interventions for Neurodevelopmental Disorders